Surgical mechanical properties of perfused decellularized massive bone allografts: An comparative in vivo test - Alicia Nuffer; Robin Evrard; Thomas Schubert; Benoit Lengelé; Alexis Veyssiere; Natacha Kadlub; Jean Boisson (PLoS ONE, 2025)
Massive bone allograft decellularized by perfusion is a solution for large bone defect reconstructions. Perfusion-based decellularization offers a solution by removing cellular components while preserving the non-immunogenic matrix. This study evaluates the in vivo integration and mechanical properties of perfusion-decellularized bone grafts compared to “fresh-frozen” grafts, both before implantation and after explantation. Standardized porcine femoral grafts were categorized into non-irradiated, irradiated, and explanted groups, with half undergoing perfusion decellularization. Biomechanical tests, including screw pull-out test, compression, and 3-point bending test, were performed. Results indicate that while decellularization increases graft brittleness, Vickers indentation and compression tests showed no significant differences between groups. In our study, decellularization reduced the mechanical strength of allografts both before and after implantation. However, since the risk of rupture occurred only under mechanical loads exceeding the physiological range, perfusion-decellularized bone grafts remain a valid strategy for bone repair.